A Thermo-Hydraulic Numerical Model for High Energy Welding Processes - Medale, Marc; Rabier, Sylvain; Xhaard, Charline (European Journal of Computational Mechanics, 2004)
A numerical model especially devoted to the thermal simulation of high energy welding processes is proposed in this paper. It suggests one possible way to overcome the difficulty to simultaneously deal in the same numerical model with solid, liquid, and gas phases, together with their intense interactions. The proposed model results in a rather simplified model in the gas phase associated with a much more detailed one in the condensed phase (solid, liquid and mushy). The resulting numerical model is based on the finite element method, and features the dynamical evolution of the gas-liquid interface (key-hole) together with the liquid-solid one through an enthalpy formulation.